Book review – essentials of economics / Dr. Muhammad Hanif Othman - Othman, Muhammad Hanif (Universiti Teknologi MARA, Kedah, 2023)
Economics is one of the humanities’ oldest fields of study. It is a branch of the social sciences that focuses on the behaviour and connections of economic actors in addition to the functioning of economies at both the micro and macro levels (Robbins, 1932). It explores the production, distribution, and consumption of goods and services; it recognises economic problems and phenomena; and it treats economic questions from both a positive (what is) and normative (what ought to be) point of view (Friedman, 1953). Essentials of Economics, the title of the book by Ahmad et al. (2022) that is the subject of this review, is both pertinent and an excellent source of reference for anyone who is considering expanding their knowledge of economics. This book provides a thorough introduction to the fundamental ideas and concepts that are central to both microeconomics and macroeconomics. The authors employed easy-to-understand phrases, pictures, examples, and case studies to help readers have a better grasp on the material. Furthermore, all of the authors had over ten years of teaching experience in a higher learning institution. Their diverse perspectives and expertise help to ensure that the book is comprehensive, up-to-date, and relevant to a wide range of students and readers. The book is well organised and written in a style that is clear and appealing. A total of 15 chapters are divided into two parts, which are microeconomics and macroeconomics. Part 1 discusses topics related to microeconomics. It first provides an overview of economics, basic economic concepts, and basic economic problems (Chapter 1). It then explains the basic concepts of demand and supply, elasticity, market equilibrium, consumer behaviour, and production in economics (Chapters 2, 3, 4, 5, and 6, respectively). Part 1 also discusses the theory of firm and market structure in detail (Chapter 7). The last chapter in this part is on the theory of distribution (Chapter 8). The second part of the book delves into macroeconomics. It first introduces macroeconomics and explains the objectives of macroeconomics (Chapter 9). Then, it discusses the concept of national output and its measurement approaches, which are the income approach, the expenditure approach, and the product or output approach (Chapter 10). It further explains the determination of national income equilibrium (Chapter 11). In addition, topics related to money, banking, and financial systems are highlighted, including the concept of money, its types, and monetary policies (Chapter 12). Public finance, which pertains to government revenue and expenditure, is also delineated (Chapter 13). Part 2 also discusses the macroeconomic problems, especially inflation and unemployment (Chapter 14), and it concludes with information about international economics (Chapter 15).